Timber-framed building damage from tephra fall and lahar : 2015 Calbuco eruption, Chile - Hayes, Josh L. (2020)
Assessing the damage to buildings from volcanic eruptions is an important aspect of volcanic risk assessment and management. However, there is a limited empirical evidence base to draw upon when describing the relation between volcanic hazard intensity and resulting physical damage. The 2015 subplinian eruption of Calbuco volcano, Chile, caused damage to buildings near the volcano because of tephra fall and lahars. Chilean authorities conducted a damage assessment of 961 properties (990 buildings) to inform an assistance programme for property owners affected by the eruption. Property assessments typically contained observations and classification of damage to a house, and in some instances accessory buildings such as sheds, garages, and exterior storage rooms. In this study we used this unique damage data set to adapt damage state frameworks for tephra fall and lahar for classifying and analysing damage observations. We developed data quality indicators to provide transparency for how we accounted for data quality issues. We assigned a tephra and/or lahar damage state to 571 buildings (530 houses and 41 accessory buildings). The 419 buildings for which we did not assign a damage state either had too little information or fell outside of tephra and/or lahar hazard zones. The minimum tephra thickness isopach band that caused complete collapse was 10 to 15 cm (dry deposit loading ~1 to 1.6 kN m−2, saturated deposit loading 1.6 to 2.4 kN m−2), but most commonly (55% of tephra exposed DS5 houses n = 11), this occurred at 15 to 30 cm (dry deposit loading ~1.5 to 3.3 kN m−2, saturated deposit loading 2.4 to 4.8 kN m−2). Lahar damage was typically described as complete (DS5), with 26 houses being swept away or destroyed around the Blanco South River. Our results add to the limited evidence base of post-eruption tephra and lahar impacts to buildings and contribute to volcanic risk and impact assessment.